2018
DOI: 10.6018/analesbio.40.03
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Pleurotus ostreatus (Jacq .: Fr.) Kummer on pear pomace: Evaluation of productivity and chemical composition of the biodegraded substrate

Abstract: El objetivo de este trabajo fue evaluar la factibilidad de emplear orujo de pera como sustrato para el cultivo comercial de dos cepas de Pleurotus ostreatus (Pl-P y Pl-J) y analizar la variación de la composición química del orujo biodegradado. La cepa Pl-J presentó 98,3% de Eficiencia Biológica, 35% de Rendimiento y 45 días de Período Productivo, mientras que para Pl-P los valores fueron 62,3%, 21,8% y 35 días, respectivamente. La actividad metabólica de ambas cepas sobre el sustrato provocó una disminución r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The decrease obtained during mycelial development is important to consider since according to Hoa et al (2015), a higher C/N ratio favours mycelium growth and a lower C/N ratio favours fruiting body growth. Previously, in fruiting body production trials with the same substrate, the authors found that the Pl-P strain caused a significant decrease in the C/N ratio (26% loss), while Pl-J practically did not modify this variable (Rodríguez et al, 2018). This variation in the C/N ratio indicates that the substrate, even after biodegradation during the mycelial development of the analysed strains (SMS), could be used in productive cycles to obtain edible carpophores.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…The decrease obtained during mycelial development is important to consider since according to Hoa et al (2015), a higher C/N ratio favours mycelium growth and a lower C/N ratio favours fruiting body growth. Previously, in fruiting body production trials with the same substrate, the authors found that the Pl-P strain caused a significant decrease in the C/N ratio (26% loss), while Pl-J practically did not modify this variable (Rodríguez et al, 2018). This variation in the C/N ratio indicates that the substrate, even after biodegradation during the mycelial development of the analysed strains (SMS), could be used in productive cycles to obtain edible carpophores.…”
Section: Discussionmentioning
confidence: 86%
“…Due to the environmental problems related to the accumulation of solid waste with a high organic content, such as the generates in the food industries related to extraction of pear juice the authors of this work investigated alternatives to reuse these wastes and involve the agricultural and environmental sectors (Martínez et al, 2015;Maldonado et al, 2018;Rodríguez et al, 2018;Maldonado et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations